A strategic management approach Education for the new world of work in South Africa - Manuel, Zelda (University of the Witwatersrand, Johannesburg, 2021)
This research investigates the readiness of the South African education system for the new world of work. The future of work will be different, driven by automation, which place employment at risk. It therefore requires educational outcomes that can prepare individuals with the correct skillset (PWC, 2019). It will demonstrate that the traditional definition of jobs is shifting , a new breed of jobs that require multiple and diverse skills will replace role specification (March & McLennan, 2017). The study used a quantitative research strategy; the data was collected from participants using a questionnaire as a data collection instrument. Descriptive statistics was used to perform the data analysis. It found that although much work was done in the tertiary education sector to prepare learners for the new world of work, respondents confirmed that they still need to continue their learning journey to remain employable in the future. An individual’s employability is dependent on effective career planning and life-long learning (M Watson, M McMahon, 2009). The research highlights that career management aim to provide a holistic approach where learners choose careers that they are passionate about and not only for employability (Maree J. G., 2009).Career counselling allows for social and economic inclusion and the absence thereof have negative impact for families and the economy (Maree J. G., 2009). Organizations need to rethink their strategies and embrace new ways of work (Magwentshu "et al", 2019).They have the responsibility to up skill and reskill their workforce in order to adapt in the future and remain profitable (PWC, 2019). South Africa has high levels of unemployment, 29% (Stats, SA, 2020) and is faced with the challenge to accelerate economic growth. A further key challenge is the pace at which local companies are prepared to compete and grow in a digital world (Magwentshu "et al", 2019). This research will assist academic institutions to prepare learners for the new world of work by identifying skills required for the 21st century workplace that will equip learners for the future. It will aid learners to research future roles prior to registration as future careers are changing and from the research results, it is clear that employability is a key factor in selecting academic courses (Chikoti, 2018)
Research report submitted in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: South African education system; employment; automation; UCTD; SDG-8: Decent work and economic growth